Comparative Analysis of the Civil Service Careers: Current Situation of Non-Academic University Staff - López-Huenante, Nicolás; Gamonal Aravena, Jorge; Tralma González, Gloria; Morales Segura, Miguel Ángel; Burgos-Bravo, Daniel (Revista del CLAD Reforma y Democracia, 2021)
Non-academic personnel in universities have been neglected in the analysis of people management. However, this university unit has a vital relevance in the operation of higher education institutions. Through a comparative analysis, this study aims to find out how the main dimensions of the civil service career of non-academic staff are regulated in different universities. The analysis considered a selection of 15 universities, both Chilean and foreign, that met the criteria of the democracy index, type of governance, from different geographical regions, state and private universities, with high performance in their countries, with documentation and existence of a formal legal act or equivalent of their policies. The results show that there is no uniformity in higher education institutions regarding how to regulate the civil service careers of non-academic personnel. This occurs because multiple instruments are used to regulate the civil service career in the different institutions and, likewise, a different number of subsystems related to this subject are covered. Finally, regardless of the regulatory mechanisms or their objectives, universities tend to guarantee a minimum number of subsystems through several instruments for the development and welfare of non-academic staff.